Risk Factors for Persistent Pain Requiring Surgical Treatment in Adult Symptomatic Accessory Navicular. Issue 3 (1st March 2021) - Park, Young Hwan; Kim, Woon; Choi, Jung Woo; Kim, Hak Jun
Abstract : Objective: Identifying the risk factors for persistent pain despite proper conservative treatment in adult symptomatic accessory navicular may reduce the need for surgical treatment. The aim of this study was to identify any such risk factors. Design: Cohort study. Setting: University hospital foot and ankle clinic. Patients: A retrospective review of 313 patients who presented with adult symptomatic accessory navicular was performed. Assessment of Risk Factors: Potential risk factors were identified via medical records and foot radiographs. The possible risk factors included age, gender, body mass index, smoking status, occurrence/cause of symptoms, occupation, type of accessory navicular, and radiographic foot parameters. Main Outcome Measures: Predictors that relate to persistent pain requiring surgical treatment in adult accessory navicular were analyzed using logistic regression analysis. Results: Of the 313 patients included, 30 (9.6%) underwent surgical treatment due to failure of conservative treatment. The odds of needing surgical treatment decreased by 0.96 per year of age at symptom onset ( P = 0.030), but those odds were 8.52 times higher in patients who had a type IIB accessory navicular ( P = 0.001). Other variables did not reach statistical significance. Conclusions: Younger age at symptom onset and type IIB were the risk factors for persistent pain requiring surgical treatment in adult symptomatic accessory navicular.